Inside the ark : the Hutterites in Canada and the United States - Kats, Yosef, 1953- (University of Regina, 2014)
In this award-winning book, Yossi Katz and John Lehr offer a thoughtful and thorough analysis of Hutterite society and seek to understand a complex and often misunderstood community.